RESEARCH ON INFORMATION TECHNOLOGY FOR DOCUMENT WORKFLOW IN VETERINARY CLINICS - Калита, Надія; Соляник, Анастасія; Пономарьова, Світлана (SWorldJournal, 2024)
The research focuses on the analysis of information technology for document workflow in veterinary clinics to enhance the efficiency of work processes. The article examines the prerequisites for implementing electronic document workflow, identifies the ma